"Reversible" myelodysplastic syndrome or ineffectual clonal haematopoiesis? – add(6p) myeloid neoplasm with a spontaneous cytogenetic remission. (October 2018) - Rady, K.; Blombery, P.; Westerman, D.A.; Wall, M.; Curtis, M.; Campbell, L.J.; Seymour, J.F.
Highlights: Myelodysplasia with a karyotypic abnormality can spontaneously regress. Clonal haematopoiesis doesn't always equate to clinically relevant disease. Observation of early clonal haematopoiesis without cytopenias is possible. Abstract: Cytotoxic chemotherapy has inherent mutagenic potential and alters the bone marrow microenvironment after therapy. In some cases, this potentiates expansion of an aberrant clone and may lead to a therapy-related myeloid neoplasm if the clone overcomes selective pressure. We present the case of a 43-year-old woman diagnosed with an indolent, therapy-related myeloid neoplasm with an isolated chromosome 6p abnormality following treatment for de novo Acute Myeloid Leukaemia (AML), who manifest a sustained spontaneous cytogenetic remission two years later, possibly due to an ineffectual or non-dominant founding clone. This case reminds us to be mindful of the possibility that clonal haematopoiesis may not always equate to clinically relevant disease, even in the setting of an abnormal clonal karyotype.